Trends in facade system overhaul based on the data analysis of procurement contracts via the PROZORRO public e-procurement system - Radkevich, A.; Netesa, K.; Tkach, T. (Ways to Improve Construction Efficiency, 2020)
Obviously, it goes without saying that sustainable economic development and an increase in the cost of energy carriers require improvements in the energy efficiency of existing buildings and structures. For this reason, intelligent energy monitoring and searching for new methods aimed at improving the performance of buildings have been of utmost importance. One of the feasible solutions to improving the performance of existing buildings would arguably be the reduction in energy costs by increasing the insulating properties of their facade systems. This paper analyses the current trends in the overhaul of facade systems in Ukraine. The research results into facade system renovation conducted via the ProZorro public e-procurement system demonstrated that a significant number of repair works were the improvements in the thermal insulation properties of facade systems by means of mineral wool panels and plaster cladding. The percentage of this type of overhaul contracts reached 67% of the total number of investigated contracts. Facade insulation renovation using expanded polystyrene plates approximately made up 20%. The restoration works of an outer layer of façade systems, including plaster restoration, spot-priming, restoration of hard putty, plaster facing and painting works, revetment, etc., which do not impact the energy efficiency of a building, made up about 13% of the total number of contracts. The area of façade works in question averaged from 200 m2 to 1500 m2. Having compared the prices per one square metre of a façade system, the average cost for such works has been calculated in the range of 1500 UAH to 2000 UAH; while the cost of advanced works ranged from 3500 UAH to 4000 UAH. Given a short maintenance-free service life of 7-10 years of the corresponding systems and guided by cost-effectiveness reasons, it has been suggested replacing these facade systems with ventilated facade systems with thermal insulation and ceramic cladding. This façade system has proved to have a significantly longer durability and maintenance-free service life, while the initial investment costs will further increase the energy efficiency properties of a building. As the result, this will enable keeping energy operating costs to minimum, which will consequently increase the building’s cost-effectiveness and its compliance with current global trends in energy conservation.